Dimensi Berpikir Kritis - Imbalan Zakaria; Suyono Suyono; Endah Tri Priyatni (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The focus of this research is the critical thinking dimension which is summarized from the opinions of seventeen experts. The dimensions of the critical thinking dimension in reasoning are interpretive, intensive, analytical, evaluative, explanatory and self-regulation. This research is a literature study of metasynthesis method. Data in the form of text quotes to seventeen experts. The results of this study are the findings of critical thinking dimensions that vary there are levels of critical thinking in two dimensions, three dimensions, four dimensions and multidimensional. Specifically, the critical thinking dimension can only be optimal if it is applied to classes that have a diversity of ideologies that have individual characteristics.Abstrak: Fokus penelitian ini adalah dimensi berpikir kritis yang disarikan dari pendapat tujuh belas ahli. Deskriptor dimensi berpikir kritis dalam penalaran adalah interpretatif, inferensif, analisatif, evaluatif, eksplanatif, dan regulasi diri. Penelitian ini merupakan penelitian kajian pustaka metode metasintesis. Data berupa kutipan teks pada tujuh belas ahli. Hasil penelitian ini temuan dimensi berpikir kritis yang bervariasi ada tingkatan berpikir kritis dua dimensi, tiga dimensi, empat dimensi dan multidimensi. Hasil penelitian secara khusus, dimensi berpikir kritis hanya bisa optimal jika diterapkan pada kelas yang memiliki keragaman ideologi yang memiliki sifat individual.